Comparison and evaluation of statistical criteria in the solar cell and photovoltaic module parameters' extraction. Issue 13 (9th November 2020) - Louzazni, Mohamed; Khouya, Ahmed; Amechnoue, Khalid; Mussetta, Marco; Crăciunescu, Aurelian
ABSTRACT: Recently, the extraction of photovoltaic parameters was the subject of intensive debate in the scientiﬁc literature. This paper presents an analysis and comparison of the use of the statistical errors in extraction of single and double diodes of the solar cell and photovoltaic module parameters. The compared errors are based on the utilisation of the firefly algorithm. The objective function used is adapted to minimise the absolute errors between the experimental and predicted current values. Two technologies of the solar cell are used to compare; a mono-crystalline silicon solar cell and the polycrystalline silicon photovoltaic module with 36 cells connected in series. The performance of the extracted parameters and current is compared with recent algorithms and techniques. The analysis and comparison of commonly used error measure help in evaluating the predictive ability of parameters extraction. The comparisons demonstrate that the firefly algorithm in statistical errors measure provides high performance and accuracy of the extracted parameters.